Development of an environmental-benign process for efficient pretreatment and saccharification of Saccharum biomasses for bioethanol production. (January 2019) - Bala, Anju; Singh, Bijender
Abstract: Saccharum biomasses ( Saccharum munja and sugarcane bagasse) were subjected to different physical, chemical and biological pretreatment methods. Physical pretreatment of lignocellulosic biomasses was carried out by using steam treatment and microwave. Chemicals pretreament of lignocellulosic biomasses were optimized by using different chemicals like alkalies and acids. Among all chemicals, ammonia treatment significantly removed lignin (approx. 77%) and removed high amount of phenolic compounds and enhanced saccharification of Saccharum munja and sugarcane bagasse. Laccase pretreatment significantly removed lignin and enhanced the reducing sugar production by 2-fold corresponding to approx. 60% saccharification of pretreated biomass as compared to other methods. Fourier-transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD) showed the removal of lignin due to pretreatments. Bio-ethanol production carried out using hydrolysate of both substrates by Saccharomyces cerevisiae and Pichia stipitis at 30 °C and 150 rpm after 72 h produced high amount of ethanol (25.06 g/L and 24.56 g/L for S. munja and sugarcane bagasse, respectively). Enzymatic hydrolysate fermented by the co-culture of S. cerevisiae and P. stipitis produced 30.78 g/L and 31.56 g/L of bioethanol from S. munja and sugarcane bagasse hydrolysate, respectively. Results indicated enhanced bioethanol production by co-culturing of pentose and hexose fermenting yeasts. Highlights: Saccharam biomasses were pretreated efficiently in a eco-friendly manner using biological methods. Pretreated biomasses were saccharified using cellulolytic and xylanolytic enzymes of Sporotrichum thermophile . FTIR, SEM and XRD studies revealed the pretreatment of lignocellulosic biomass. Enzymatic hydrolysate was co-fermented by hexose and pentose fermenting yeasts to bioethanol.